THE ROLE OF EMPLOYEE DEMOGRAPHICS, WORK STRESS, AND REWARDS ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE - Ratri, Kinanthi Gusti Reina; Wahjudono, Denny Bernardus Kurnia (Jurnal Aplikasi Manajemen, 2021)
This research was conducted at a private university in East Java (University X). The purpose of this study was to examine demographic factors as moderating variables on the relationship between job stress and job satisfaction and the relationship between rewards and job satisfaction and measure the effect of job satisfaction on job performance at the university. 106 administrative staff and 101 lecturers are the samples in this study. The sampling technique was employed using simple random sampling. Structural Equation Model used to analyze the multivariate data. Results showed that employee demographics of both respondents do not act as moderators on the relationship between job stress and job satisfaction and the relationship between rewards and job satisfaction. Likewise, the job satisfaction variable in this study does not provide a mediating effect on the relationship between job stress and employee performance and the relationship between rewards and employee performance. Significant results for administrative staff are shown in the relationship between rewards and job satisfaction and the relationship between rewards and employee performance. As for lecturers, significant results are shown in the relationship between job stress and performance and the relationship between reward and job satisfaction. Further research suggested conducting workload analysis for each position, developing an appropriate reward system, further research to determine the factors that can predict performance, and research continued by using unstructured demographic data, such as income levels or workloads.